Molecular mechanisms of bi-directional ion transport in the Malpighian tubules of a lepidopteran crop pest, Trichoplusia ni. (August 2018) - Kolosov, Dennis; Tauqir, Maria; Rajaruban, Sabitha; Piermarini, Peter M.; Donini, Andrew; O'Donnell, Michael J
Graphical abstract: Highlights: Novel ion transport mechanisms in lepidopterans described. Na + /K + -ATPase localizes to principal cells in lepidopteran Malpighian tubule. K + channels play an important role in ion secretion in lepidopteran MTs. Ion transport reversal includes shutdown of ion-secretory transport. Gap junction coupling likely in toggling between ion secretion and reabsorption. Abstract: Classical studies have described in detail the complex and regionalized morphology of the Malpighian tubule (MT) in larval Lepidoptera. Recent studies revealed unusual aspects of ion transport in the Malpighian tubules of the larva of the cabbage looper, Trichoplusia ni . These included: cation reabsorption via secondary cells (SC); coupling of SCs to neighbouring PCs via gap junctions to enable reabsorption; and a reversal from cation secretion to reabsorption by the principal cells in the distal ileac plexus region of the in situ tubule in response to dietary ion loading. The current paper aimed to identify molecular components of ion transport in the MTs of T. ni and to describe their role in the recently reported reversal of ion transport in ion-loaded animals. Using a combination of molecular, immunohistochemical and electrophysiological techniques, we assigned roles to Na + /K + -ATPase (NKA), V-type H + -ATPase (VA), Na + /K + /Cl − co-transporter (NKCC), K + /Cl − co-transporter (KCC), inward-rectifying K + channel (Kir), and Na + /H + exchangers (NHE)-7 and -8 in the transport of Na + and K + by the distal ileac plexus of T. ni . The yellow region of the tubule lacked all of the above except VA, and the white region lacked all of the above transporters but expressed an amiloride-sensitive Na + channel (NaC). Overall, the ion transport machinery in the distal ileac plexus of the T. ni tubule shows remarkable similarity to that in tubules of other groups of insects, yet this region transports ions very differently. Shutdown of secretory ATPases and utilisation of the same molecular machinery in the face of changing ion gradients may enable ion transport reversal in lepidopteran MTs. We propose that gap junction-based coupling of the two cell types likely aids in toggling between ion secretion and ion reabsorption in this segment.